A Longitudinal Study of Insomnia and Other Sleep Complaints in Adolescents With and Without Alcohol Use Disorders. (27th June 2014) - Hasler, Brant P.; Martin, Christopher S.; Wood, D. Scott; Rosario, Bedda; Clark, Duncan B.
<x xml:space="preserve">Abstract</x> Background Sleep disturbances are both common and well‐characterized in adults with alcohol use disorders (AUDs), but have received little study in adolescents with AUDs. Furthermore, a handful of studies suggest that sleep complaints are a risk factor for AUDs. However, no published studies have yet examined the longitudinal course of sleep complaints in adolescents with AUDs; in particular, it remains unclear how persistent AUD‐associated sleep complaints are in this age group, and what types of sleep complaints are most relevant to alcohol‐use symptoms. We investigated these questions in a 5‐year longitudinal study of adolescents with and without AUDs at baseline. Methods Participants were 696 adolescents (age 12 to 19) from a longitudinal study at the Pittsburgh Adolescent Alcohol Research Center. At baseline, 347 participants had a current AUD (AUD+), while 349 had no current or past AUD (AUD−). We examined sleep and alcohol involvement at baseline as well as 1‐, 3‐, and 5‐year follow‐up visits. Sleep variables included self‐reported insomnia and hypersomnia, as well as variability in weekday–weekend sleep duration, all at baseline. Covariates included sex, age, current alcohol symptoms, and depression severity. Results The AUD+ group reported more overall sleep disturbance at baseline, including greater insomnia and hypersomnia complaints, and greater variability in weekday–weekend sleep duration. Group differences in insomnia and hypersomnia complaints persisted to the 5‐ and 3‐year follow‐ups, respectively. In the AUD− group, greater insomnia complaints at baseline predicted an increase in alcohol symptoms at the 1‐year follow‐up, while greater variability in sleep duration at baseline predicted an increase in alcohol symptoms at the 3‐ and 5‐year follow‐ups. Conclusions These results complement previous findings in other samples, indicating that insomnia and other sleep problems are a chronic predicament for adolescents with AUDs. The findings also suggest that sleep disturbances may place adolescents without AUDs at an elevated risk of developing alcohol problems.